2010
DOI: 10.1074/jbc.m109.070706
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation in Hypothalamic Pro-opiomelanocortin Neurons Is Essential in Illness- and Leptin-induced Anorexia

Abstract: Anorexia and weight loss are prevalent in infectious diseases. To investigate the molecular mechanisms underlying these phenomena, we established animal models of infection-associated anorexia by administrating bacterial and viral products, lipopolysaccharide (LPS) and human immunodeficiency virus-1 transactivator protein (Tat). In these models, we found that the nuclear factor-B (NF-B), a pivotal transcription factor for inflammation-related proteins, was activated in the hypothalamus. In parallel, administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 44 publications
2
73
1
2
Order By: Relevance
“…administration of LPS activated hypothalamic NFkB by increasing the phosphorylation of the p65 subunit, the higher level of NFkB in the nucleus, and the upregulated expression of POMC may imply that the translocation of NFkB from cytoplasm into nucleus is related to the transcription of target genes such as POMC during LPS stimuli. These findings (Campo et al 2010, Jang et al 2010, Deshpande et al 2011 collectively imply that NFkB activation in the hypothalamus plays a critical role in LPS-induced anorexia.…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducmentioning
confidence: 76%
See 1 more Smart Citation
“…administration of LPS activated hypothalamic NFkB by increasing the phosphorylation of the p65 subunit, the higher level of NFkB in the nucleus, and the upregulated expression of POMC may imply that the translocation of NFkB from cytoplasm into nucleus is related to the transcription of target genes such as POMC during LPS stimuli. These findings (Campo et al 2010, Jang et al 2010, Deshpande et al 2011 collectively imply that NFkB activation in the hypothalamus plays a critical role in LPS-induced anorexia.…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducmentioning
confidence: 76%
“…A recent study has revealed that NFkB directly bound the POMC gene to promote transcription in response to LPS stimulation (Jang et al 2010), and meanwhile, the transcriptional level of NFkB was upregulated by LPS treatment in the hypothalamus. Nuclear translocation of NFkB has been shown to be insufficient for the maximal activation of NFkB (Chen & Greene 2004).…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducmentioning
confidence: 99%
“…However, activation of hypothalamic NF-κB signalling can also promote Pomc transcription and induce weight loss and food intake reduction [24]. Moreover, constitutively active RELA triggers severe TNF-α-dependent inflammation, which leads to small sized and lean mice on a Tnfr1 (also known as Tnfrsf1a) −/− background [25].…”
Section: Resultsmentioning
confidence: 99%
“…Acute inflammation leads to activation of POMC neurons [100], increased expression of MC4R [101] and increased POMC expression [102,103] as shown in models of LPS and IL-1␤ -induced anorexia. Consequently, counteracting the activation of the melanocortin system by MC4R antagonism prevented the development of LPS-induced anorexia [102,104,105].…”
Section: Hypothalamic Inflammation: Anorexigenic Signallingmentioning
confidence: 95%